Pengaruh Negatif Era Teknologi Informasi dan Komunikasi pada Remaja (Perspektif Pendidikan Islam) - Ali Rahman (Al-Ishlah: Jurnal Pendidikan Islam, 2016)
The development of information and communication technologies can no longer be avoided. Due to the presence of information and communication technology, one's life will be easier. Someone can send a message, send and find information quickly and easily. But behind the convenience to be aware of any negative impact of information and communication technology to teenagers. In this era of information and communication technology, every business and activities as well as a deliberate act to achieve a goal must have a foundation footing good and strong. Islamic education as a form of human effort, must have a foundation to which all activities and all the formulation of educational goals of Islam is connected. Islamic religious education in overcoming the negative influence of the era of information and communication technologies in adolescents are educators especially for the elderly or people who provide supplies knowledge of Islam against teenagers so that they can fortify themselves in the act, think, and act in accordance with the provisions outlined by Allah SWT. for the safety of his life.